Evaluation the Door-to-Balloon Time in Patient with STElevation Myocardial Infraction (STEMI) in King Abdullah Medical City (KAMC) in Makkah Almukarramah: A Retrospective Single Center Study (Medico Legal Update, 2021)
Background: ST-Elevation Myocardial Infarctionis a time-sensitive emergency condition. Thus, guidelinesrecommended 90 minutes or less for door-to-balloon time at a percutaneous coronary intervention-capablehospital and with in 120 minutes or less if transferred from per cutaneous coronary intervention-UncapableHospital. The main objective was to evaluate the recommended time needed forreperfusion therapyparticularly percutaneous coronary intervention inpatients with ST-Elevation Myocardial Infarctionat KingAbdullah Medical City.Method and Results: A retrospective single center study. Data were obtained from 47 patients recordsdiagnosed with ST-Elevation Myocardial Infarction and treated with percutaneous coronary interventionatKing Abdullah Medical Cityfrom Jan 2018 through March 2019. About 36.4% of patients receivedpercutaneous coronary intervention in more than 90 Minutes eventhough they arrived directly at KingAbdullah Medical City. For patients who were transferred to King Abdullah Medical City, 63.9% of thosepatients did not achieve the recommended door-to-balloon time.Conclusion: High percentage of patients with ST-Elevation Myocardial Infarctionat King Abdullah MedicalCity did notreceive percutaneous coronary intervention within the recommended timeline.